CHALLENGES AND OPPORTUNITIES IN PREPARING PROSPECTIVE TEACHERS IN THE DIGITAL ERA: A CRITICAL STUDY BASED ON DIGITAL LITERACY PROFILE - Sele, Yunawati; Dewi, Ni Putu Yuni Astriani (JURNAL EDUSCIENCE, 2025)
Purpose—The preparation period for prospective teachers at the Teacher Training Institute begins with preparing them to navigate the digital era. Digital literacy is a crucial competency that needs to be effectively developed during this period. This study aimed to evaluate the opportunities and obstacles associated with preparing prospective teachers for the digital era by examining their digital literacy profiles.Methodology—This research employed a quantitative descriptive research design involving 250 students from the Faculty of Teacher Training and Education at Timor University. We conducted the research in three stages: preparation, implementation, and final. The research data, obtained through a digital literacy questionnaire, underwent quantitative descriptive analysis.Findings – The study's results indicated that prospective teachers' average digital literacy score was 73.86, with 60% of respondents falling into the "good" category. However, only 13.6% of respondents exhibited digital literacy in the "outstanding" category. We classified 26.4% of respondents as "fairly good," "bad," and "very bad." This variation suggests a gap that must be rectified by optimizing internal factors, such as student self-awareness, and external factors, such as technology-based training and increased access to digital devices. The curriculum for prospective teacher education should prioritize the enhancement of digital literacy.Significance—Consequently, to establish an environment that motivates the enhancement of digital literacy, it is imperative that educational institutions, the government, and the private sector collaborate. Internally, Teacher Training Institutions must ensure the development and implementation of project-based curricula that effectively integrate technology to prepare prospective teachers for digital literacy and 21st-century skills.